2015
DOI: 10.5194/angeo-33-1031-2015
|View full text |Cite
|
Sign up to set email alerts
|

Observation of a new type of low-frequency waves at comet 67P/Churyumov-Gerasimenko

Abstract: Abstract. We report on magnetic field measurements made in the innermost coma of 67P/Churyumov-Gerasimenko in its low-activity state. Quasi-coherent, large-amplitude (δB/B ∼ 1), compressional magnetic field oscillations at ∼ 40 mHz dominate the immediate plasma environment of the nucleus. This differs from previously studied cometary interaction regions where waves at the cometary ion gyrofrequencies are the main feature. Thus classical pickup-iondriven instabilities are unable to explain the observations. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
89
2

Year Published

2016
2016
2017
2017

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 73 publications
(102 citation statements)
references
References 25 publications
11
89
2
Order By: Relevance
“…2. Section 3 includes the temporal and spatial evolution of wave properties and thus extends the findings presented in Richter et al (2015) using also later observations. Particularly the energy density in a certain frequency band is a well-proven means to characterize wave properties and to compare wave observations made by different instruments at different locations.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…2. Section 3 includes the temporal and spatial evolution of wave properties and thus extends the findings presented in Richter et al (2015) using also later observations. Particularly the energy density in a certain frequency band is a well-proven means to characterize wave properties and to compare wave observations made by different instruments at different locations.…”
Section: Introductionmentioning
confidence: 69%
“…The shown waves are characterized by amplitudes of ∼ 6 nT, a δB/B ∼ 1 , and frequencies of ∼ 28 mHz. These amplitude and frequency values are typical for the newly detected lowfrequency waves at 67P/C-G and first described by Richter et al (2015). In order to systematically investigate the temporal and spatial evolution of the wave activity, the energy density in the 10-100 mHz band has been calculated by integrating the power spectral density for almost 9000 hourly intervals.…”
Section: Evolution Of Wave Activity Deduced From Long-term Rpcmag Obsmentioning
confidence: 77%
“…During the period discussed in this paper the outgassing rate is around 10 27 molecules s −1 , which is several orders of magnitude smaller than at comets 27P/GriggSkjellerup or 1P/Halley (Reinhard, 1986). This means that the interaction of the solar wind with the outgassing comet is different, which was clearly illustrated through the discovery of the "singing comet" by Richter et al (2015), an unexpected plasma instability created by the not-yet-magnetized freshly produced ions near the comet. This is the context in which the results of this paper should be interpreted: measurements much closer to a cometary nucleus than ever before, with low outgassing rate and a very slowly moving spacecraft relative to the nucleus.…”
Section: Discussionmentioning
confidence: 88%
“…The data from RPC MAG have been calibrated, however Richter et al (2015) state that: "The short boom length implies that the spacecraft is heavily contaminating the magnetic field measurements. At this stage of the investigation it was not possible to completely remove these quasi-static spacecraft bias fields from the measured magnetic field values.".…”
Section: Discussionmentioning
confidence: 99%
“…At this time the water production rate was slightly below the strongest limits on MBCs to date, at 1 × 10 25 mol s −1 , and outgassing was not detectable from Earth (via sensitive searches for CN with large telescopes- Snodgrass et al 2016;Opitom et al 2017). This is the lowest activity comet environment ever visited by a spacecraft, with all previous mission performing fast flybys at ∼ 1 au, and there were some surprising results: the Rosetta Plasma Consortium instruments discovered oscillations in the magnetic field at around 40 mHz attributed to interactions with cometary ions and the solar wind (Richter et al 2015), the so-called 'singing comet' based on the public release of an audio version of this interaction. Feldman et al (2015) show that emission lines from atomic hydrogen and oxygen, observed by the Alice instrument in the UV, could only be explained by electron impact dissociation rather than the more typical photodissociation seen in cometary comae.…”
Section: Rosettamentioning
confidence: 98%